Application of a Physiologically Based Pharmacokinetic Model to Predict OATP1B1‐Related Variability in Pharmacodynamics of Rosuvastatin. (9th July 2014) - Rose, RH; Neuhoff, S; Abduljalil, K; Chetty, M; Rostami‐Hodjegan, A; Jamei, M
Abstract : Typically, pharmacokinetic–pharmacodynamic (PK/PD) models use plasma concentration as the input that drives the PD model. However, interindividual variability in uptake transporter activity can lead to variable drug concentrations in plasma without discernible impact on the effect site organ concentration. A physiologically based PK/PD model for rosuvastatin was developed that linked the predicted liver concentration to the PD response model. The model was then applied to predict the effect of genotype‐dependent uptake by the organic anion‐transporting polypeptide 1B1 (OATP1B1) transporter on the pharmacological response. The area under the plasma concentration–time curve (AUC0–∞ ) was increased by 63 and 111% for the c.521TC and c.521CC genotypes vs. the c.521TT genotype, while the PD response remained relatively unchanged (3.1 and 5.8% reduction). Using local concentration at the effect site to drive the PD response enabled us to explain the observed disconnect between the effect of the OATP1B1 c521T>C polymorphism on rosuvastatin plasma concentration and the cholesterol synthesis response. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e124; doi:10.1038/psp.2014.24 ; published online 09 July 2014